HUBUNGAN KELAINAN LETAK JANIN DAN KEHAMILAN GANDA DENGAN KEJADIAN KETUBAN PECAH DINI DI RUMAH SAKIT UMUM DAERAH KOTA KENDARI - Saida, Saida; Ayu Syakila Rachmad, Alda (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Premature rupture of membranes (PROM) refers to the rupture of membranes before the onset of labor. PROM is a serious problem in obstetrics. The incidence of PROM worldwide ranges from 5% to 10%. Additionally, various risk factors can also cause PROM, such as gestational age, gestational spacing, abnormal fetal position, and multiple pregnancies. The purpose of this study was to analyze the factors associated with the incidence of premature rupture of membranes in laboring mothers at the Kendari City Regional General Hospital. This study is an observational analytic study with a cross-sectional design. Data were obtained by observing medical records. The sample of this study was pregnant women who entered the delivery room at Kendari City Hospital in 2022. The sampling technique used was simple random sampling. The dependent variable in this study was premature rupture of membranes, and the independent variables were abnormal fetal position and multiple pregnancies. Data were analyzed using the Chi-square test. The results of the analysis showed that there was a relationship between abnormal fetal position (p = 0.040) and multiple pregnancies (p = 0.076). There is a significant relationship between abnormal fetal position and the incidence of premature rupture of membranes, while multiple pregnancies are not related to the incidence of premature rupture of membranes at the Kendari City Regional General Hospital.